The Existence of a N→C Dative Bond in the C60 -Piperidine Complex - Lamanec, Maximilián; Lo, Rabindranath; Nachtigallová, Dana; Bakandritsos, Aristides; Mohammadi, Elmira; Dračínský, Martin; Zbořil, Radek; Hobza, Pavel; Wang, Weizhou (Angewandte Chemie (International ed. in English), 2021)
The complexes formed between carbon allotropes (C20 , C60 fullerenes, graphene, and single-wall carbon nanotubes) and piperidine have been investigated by means of computational quantum chemical and experimental IR and NMR techniques. Alongside hydrogen bonds, the C⋅⋅⋅N tetrel bond, and lone-pair⋅⋅⋅π interactions, the unexpected N→C dative/covalent bond has been detected solely in complexes of fullerenes with piperidine. Non-planarity and five-member rings of carbon allotropes represent the key structural prerequisites for the unique formation of a dative N→C bond. The results of thermodynamics calculations, molecular dynamics simulations, and NMR and FTIR spectroscopy explain the specific interactions between C60 and piperidine. The differences in behavior of individual carbon allotropes in terms of dative bonding formation brings a new insight into their controllable organic functionalization.
Keywords: piperidine; covalent functionalization; N→C dative bonds; hydrogen bonds; fullerenes